Chinese IPOs Market in Global Financial Crisis - Mahmood, Faiq; Xinping, Xia; Shahid, Humera (Indian Journal of Finance, 2010)
This study investigates Chinese stock market performance in context of IPOs during and before global financial crisis. Underpricing and performance of the Chinese IPOs and stock markets (Shanghai and Shenzhen stock exchange) is analyzed in two time windows i.e. one before global financial crisis (2004-2006) and other during the crisis period (2007-2009). Market adjusted first day return of 72.62% and 145.20% is observed in pre crisis and during crisis periods respectively. It is interesting to note that short-run performance of market adjusted returns during crisis is much better than pre -crisis. During 2007-2009, IPOs activity is more (246 IPOs) as compared to 2004-2006 (180 IPOs). In addition, the percentage of financing through IPOs increased as compared to pre crisis period. Although the phenomena of crisis significantly affected the Chinese stock market where the indices falls to a lower level of 6000 in Shenzhen and 2000 in Shanghai stock exchange, it did not drastically affect the market and performance of new issues. An extensive research has been carried out on IPO underpricing in both developed and developing economies. However, it is not analyzed in context of global financial crisis. The stock market adjusted first day returns are used in the research as the proxy for underpricing of IPOs. The study carried out this work as it is the biggest phenomena in the current financial world.